Culturally Effective Care for Refugee Populations: Interprofessional, Interactive Case Studies - Shannon N. Fitzgerald; Katie F. Leslie; Ryan Simpson; V. Faye Jones; Elizabeth Tatum Barnes (Association of American Medical Colleges, 2018)
Introduction Within health sciences education literature, the majority of reported student experiences with refugee populations are limited to traditional, professionally independent, elective courses and extracurricular volunteer opportunities. A simulated patient exercise is a learning opportunity that helps participants engage with material in real time in a realistic environment, demanding higher levels of learning. This session utilized a simulated patient facilitator in interprofessional small groups to explore common health needs and barriers to care among refugee populations. Methods Health professions students from nine degree programs participated in a refugee health session in interprofessional teams of nine to 10 students to explore patient cases. The session concluded with a debriefing discussing the outcomes of the student-patient interaction, best practices, and exemplary practice models as takeaways. The simulated patient facilitators completed an Observation Checklist to assess students' grasp of learning objectives. Results Five hundred twenty-four students participated in the refugee session, divided into 61 groups. Observation Checklists were completed for 58 groups (95%). Assessment of student engagement focused on general health needs common to refugee populations: barriers to health care, team and individual roles, bias, consequences of nontreatment, and social determinants of health. Most of the groups (95%) reported engagement between the simulated patient facilitator and the group of student providers. Qualitative data indicated student groups were knowledgeable in each of the overarching learning objectives. Discussion This session allowed health sciences students to focus on culturally effective patient care for refugee populations as a part of an interprofessional team.